Biology of Saccular Cerebral Aneurysms: A Review of Current Understanding and Future Directions - Fennell, Vernard S.; Kalani, M. Yashar S.; Atwal, Gursant; Martirosyan, Nikolay L.; Spetzler, Robert F. (Frontiers in Surgery, 2016)
Understanding the biology of intracranial aneurysms is a clinical quandary. How these aneurysms form, progress, and rupture is poorly understood. Evidence indicates that well-established risk factors play a critical role, along with immunologic factors, in their development and clinical outcomes. Much of the expanding knowledge of the inception, progression, and rupture of intracranial aneurysms implicates inflammation as a critical mediator of aneurysm pathogenesis. Thus, therapeutic targets exploiting this arm of aneurysm pathogenesis have been implemented, often with promising outcomes.